2009
DOI: 10.1111/igc.0b013e3181a44bc8
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modified Heparin Inhibits In Vitro L-Selectin-Mediated Human Ovarian Carcinoma Cell Adhesion

Abstract: Accumulating evidence indicates that hematogenous metastasis is facilitated by tumor cell-leukocyte emboli formation, and L-selectin plays a major role in the process. Several independent studies have indicated that tumor metastasis can be inhibited by chemically modified heparin with low anticoagulant activity in the different tumor models. In the present study, we demonstrated that chemically modified nonanticoagulation heparin derivate (periodate-oxidized, borohydride-reduced heparin [RO-heparin]) can inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Likewise, the mentioned inhibitory interaction of heparins with selectins is independent of the anticoagulant function of heparin and was described also for chemically modified forms of heparin in vitro. 79 As the hemostatic system is involved in cancer development, it remains to be proven what the true therapeutic value of inclusion of nonanticoagulant heparin in cancer treatment is and what the best treatment strategy is in current clinical practice. Hence, the possibility that different types of heparin have different therapeutic effects in various types of cancer should be considered.…”
Section: Antimetastatic Properties Of Heparinmentioning
confidence: 99%
“…Likewise, the mentioned inhibitory interaction of heparins with selectins is independent of the anticoagulant function of heparin and was described also for chemically modified forms of heparin in vitro. 79 As the hemostatic system is involved in cancer development, it remains to be proven what the true therapeutic value of inclusion of nonanticoagulant heparin in cancer treatment is and what the best treatment strategy is in current clinical practice. Hence, the possibility that different types of heparin have different therapeutic effects in various types of cancer should be considered.…”
Section: Antimetastatic Properties Of Heparinmentioning
confidence: 99%
“…However, they did not show data on selectin and inhibi-tion of tumor growth. In addition, Chen and co-workers reported that chemically modified heparin derivate significantly inhibited L-selectin binding to human overian cancer cells [71]. Our work in this study was focused on antitumor growth, revealing that p53-Rb-E2F pathway was involved in this inhibition of lung cancer tumor growth.…”
Section: Discussionmentioning
confidence: 75%
“…At present, many methods are used to construct the new agents targeting cancer therapy, such as the Valeraldehyde method, the sodium periodate method [36,37], and nanoparticles. However, the isomers were produced and difficultly purified.…”
Section: Discussionmentioning
confidence: 99%